Upaya Peningkatan Pemahaman Konsep Rangkaian Listrik Sederhana dengan Model Pembelajaran Experiential Learning di Kelas VI SDN Plosokerep 2 Kota Blitar - Hetty Imro’ah (IJoIS: Indonesian Journal of Islamic Studies, 2022)
Natural Sciences is a subject in elementary school which is intended so that students have organized knowledge, ideas and concepts about the natural surroundings, which are obtained from experience through a series of scientific processes including investigation, compilation and presentation of ideas. In science learning about Electrical Circuits in class VI SDN Plosokerep 2, Sananwetan District, Blitar City, it can show poor learning outcomes. Learning outcomes can be seen from 17 students who achieved completeness only 7 students or 41% with a classical average value of 51. This value is due to a lack of learning by doing separate experiences and only using conventional learning methods. In this case, the sixth grade teacher conducts classroom action research with qualitative descriptive research, with a learning method that seeks to increase students' conceptual understanding. Experience-Based Learning Method (Experiential Learning) is a model of the teaching and learning process that activates learners to build knowledge and skills through direct experience.